1963
DOI: 10.1577/1548-8659(1963)92[146:ucosfp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Census of Stream Fish Populations

Abstract: Variability and reliability of counts of fish made by divers in sections of two British Columbia rivers are examined. Repeated counts of several species of fish by a team of divers in a stream section are reasonably homogeneous, and not markedly different from total numbers subsequently recovered by poisoning. Diver counts of large spawning rainbow trout also agree closely with those made in areas with good visibility from the river bank or from helicopter. Under suitable conditions a diver team can rapidly ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 0 publications
3
42
2
Order By: Relevance
“…The proportion of the adult trout population seen by drift divers in the Owen and Ugly Rivers (20-60%) was similar to that reported in several other studies (10-40%; Northcote & Wilkie 1963;Palmer & Graybill 1986;Slaney & Martin 1987) and only slightly lower than that reported (64-77%) by Barker (1988). It is possible that the upstream crawl diving technique used in Barker's study is more efficient than drifting down stream with the current, especially in small relatively shallow rivers.…”
Section: Accuracy Of Drift-dive Estimatessupporting
confidence: 89%
See 1 more Smart Citation
“…The proportion of the adult trout population seen by drift divers in the Owen and Ugly Rivers (20-60%) was similar to that reported in several other studies (10-40%; Northcote & Wilkie 1963;Palmer & Graybill 1986;Slaney & Martin 1987) and only slightly lower than that reported (64-77%) by Barker (1988). It is possible that the upstream crawl diving technique used in Barker's study is more efficient than drifting down stream with the current, especially in small relatively shallow rivers.…”
Section: Accuracy Of Drift-dive Estimatessupporting
confidence: 89%
“…Direct methods of assessing the accuracy of underwater census, such as poisoning (Northcote & Wilkie 1963;Hillman et al 1992) or dewatering a reach after dives (Palmer & Graybill 1986) have indicated that a large proportion offish are usually missed by divers (30-80%). In small rivers, where electro-fishing is possible, diver counts have generally been lower than population estimates calculated from electro-fishing (Cunjak et al 1988;Hankin & Reeves 1988;Hayes & Baird 1994;Pert et al 1997;Grost & Prendergast 1999).…”
Section: Introductionmentioning
confidence: 99%
“…That is, capture rates of fish via electrofishing will vary with factors such as: fish density, fish behavior and size; habitat structure; environmental conditions (e.g., stream temperature, turbidity, etc. ); sampling gear; and size of sampling unit (e.g., see Northcote and Wilkie 1963, Mesa and Schreck 1989, Rodgers et al 1992, Bayley and Dowling 1993. One or more of these factors can vary both spatially and temporally.…”
Section: Removal Estimates As Complete Countsmentioning
confidence: 99%
“…Rodgers and others (1992) concluded that because the relative accuracy of snorkel estimates varies from stream to stream, snorkel counts should be regularly calibrated with other methods of estimating population size. The accuracy of underwater estimates has been estimated by comparing snorkel counts with abundance estimates derived from electrofishing (Griffith 1981;Hankin and Reeves 1988), seining (Goldstein 1978), and toxicants (Hillman and others 1992;Northcote and Wilkie 1963). Slaney and Martin (1987) and Zubik and Fraley (1988) reported a technique that combines snorkeling and markrecapture estimates and can be used to calibrate snorkel counts in remote streams (see Snorkeling Procedures, Mark-Recapture Estimates).…”
Section: Precision and Accuracymentioning
confidence: 99%
“…Precise estimates of fish abundance can be obtained using underwater counts (Griffith 1981;Northcote and Wilkie 1963;Schill and Griffith 1984;Zubik and Fraley 1988). However, several factors, including the behavior of the target fish species and attributes of the physical habitat (stream size, water clarity, temperature, and cover), can bias results.…”
Section: Introductionmentioning
confidence: 99%